The Effectiveness of Using E-Comics to Enhance Arabic Reading Skills: A Quasi-Experimental Study at Nurul Hikmah Islamic Junior High School, East Jakarta - Achmad Cholip; Azmy Ali Mucthar; Tahir Wijaya (Universitas Islam Negeri Madura, 2026)
This study aimed to investigate the effectiveness of e-comic media in improving the Arabic reading skills of eighth-grade students at Nur Al-Hikmah Islamic Junior High School, East Jakarta. The study was motivated by students’ low interest and limited proficiency in Arabic reading, as well as the lack of interactive learning media used in classroom instruction. A quantitative approach employing a quasi-experimental method with a one-group pretest–posttest design was applied. The sample consisted of 25 eighth-grade students. Data were collected through observation, documentation, and pretest–posttest assessments and were analyzed using a paired-sample t-test. The findings revealed a significant improvement in students’ reading performance, with the mean score increasing from 62.16 in the pretest to 72.60 in the posttest. Statistical analysis indicated that the calculated t-value (13.865) exceeded the critical t-value (2.0638), with a significance value below 0.05. Therefore, e-comic media was found to be effective in enhancing students’ Arabic reading skills.